The Influence of Service Quality on inpatients Satisfaction: Study at Bahagia Hospitals, Makassar City - Herlina Sakawati; Nina Agustina; Sulmiah Sulmiah (Jurnal Office, 2021)
This study aims to determine the effect of service quality on inpatient satisfaction at the Bahagia Hospital in Makassar City. The research method used is a quantitative survey method using an explanatory approach. A sample of 100 people who are inpatients at the Bahagia Hospital using accidental sampling technique. The data analysis used is descriptive analysis and inferential analysis. The results showed that the quality of service had a significant influence on the satisfaction of inpatients at the Bahagia Hospital. This shows that service quality has an important role so that service delivery can provide results in accordance with what patients expect